Impact of Postpartum Dexamethasone on Postpartum Disease Stabilization in Women with HELLP Syndrome - Ayla Sargın Oruç; Figen Türkçapar; Serdar Oğuz; Necati Hançerlioğulları; Ümit Bilge; Nuri Danışman (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the impact of postpartum corticosteroid therapy on maternal disease in women with HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome.